Impact of poverty alleviation projects on rural women in Bohlabela : Limpopo Province - Tshabangu, Siphiwe Noster (University of Limpopo (Turfloop Campus), 2005)
The purpose of this study was to explore women’s involvement in poverty alleviation projects and to examine the benefits that are derived from such projects. The Phutuma Development Project and Gottenburg Women’s Group are the projects which were studied. The methods used to conduct this study involved collecting data through questionnaires and interviews. The various stakeholders, project members as well as government officials from the departments of Health and Social Development were interviewed. This study is significant in that it can help the government in its efforts to assist the poor live a decent life, and to provide better services to communities. This study uncovers the kind of challenges that government departments and communities face when setting up poverty alleviation projects. The study recommends how this should be done to achieve optimum results.
Thesis (M.Dev.) --University of Limpopo, 2005
Keywords: Poverty alleviation; Rural women; 338.968; Rural poor; Economic development projects